Pengembangan Strategi Pemanfaatan Media Sosial Dalam Penerimaan Mahasiswa Baru - Muhammad Faisal Rahman; Juliana Kurniawati; Fitri Nur Hafidzah (STAI Bumi Silampari, 2025)
This study aims to formulate development strategies to optimize social media use in supporting the student admission process at Universitas Muhammadiyah Bengkulu (UMB). Using a mixed-methods approach, quantitative data were gathered from 100 respondents via online questionnaires, while qualitative data were obtained from 16 purposively selected informants through interviews. The analysis employed SWOT, IFE (Internal Factor Evaluation), and EFE (External Factor Evaluation) frameworks. Results identified 12 strategies classified into SO, WO, ST, and WT categories. With an IFE score of 2.79 and an EFE score of 2.64, UMB falls into Quadrant V, indicating a